A cephalometric study to determine the plane of occlusion in completely edentulous patients - Amit D Hindocha; Vikas N Vartak; Aruna J Bhandari; Mohit T Dudani (Wolters Kluwer Medknow Publications, 2013)
Aim: Determination of the plane of occlusion in completely edentulous patients with the help of the ala-tragus line (Camper's plane) may be questioned. An attempt to devise an alternative method to determine the orientation of the plane of occlusion was made. Materials and Methods: Cephalometric analysis was used to identify whether a correlation exists between the plane of occlusion of dentulous Indian individuals and other stable cranial landmarks. Results: A negative correlation was found to exist between the occlusal Plane-FH plane angle and the porion-nasion-anterior nasal spine (PoNANS) angle. Conclusions: From the derived mathematical correlation, it was concluded that the angulation of the occlusal plane in completely edentulous subjects may be determined by taking a cephalogram at the diagnostic stage. Further, the clinical applicability of the derived mathematical formula (while determining the plane of occlusion) was tested on completely edentulous patients.